Construction of an indicator library for cities’ sustainable development - Maomao Yan; Feng Yang; Lingna Liu; Dehua Guo; Chao Li (Chinese Journal of Population, Resources and Environment)
Cities are key to countries’ strategies for achieving the UN’s sustainable development goals (SDGs). In China, evaluating cities’ sustainable development (CSD) processes and abilities requires establishing an indicator library for cities’ sustainable development (ILCSD). Based on the SDG framework, and referring to typical evaluation systems and international standards, this study proposes an ILCSD, aiming to promote new urbanization and high-quality development in China. Using a step-by-step “eliminate–replace–augment” indicator selection method that takes mature indicators from existing standards for city evaluation, we form an ILCSD that responds to the SDGs while meeting China’s specific needs. Using the ILCSD, cities can select a set of indicators to assess and monitor their strengths and weaknesses. Through empirical analysis, we verify the feasibility of using ILCSD to construct a CSD evaluation system for Beijing, China. For the first time, ILCSD has established a mapping relationship between the core indicators from domestic and foreign standards of city development and the SDGs . It provides a tool for cities in different regions, at different stages of development and with different endowment types to select high-quality indicators according to local conditions, effectively solving the “last mile” problem of SDGs implementation at the city level. In the process of implementing indicators, we further suggest that important indicators with incomplete statistical data should nevertheless be included in the scope of cities’ statistical monitoring. This study’s findings can facilitate China’s contribution to global sustainable development indicators and to future revisions of international standards.